Implementasi Etika Di Lingkungan Mahasiswa Ditinjau Dari Sudut Pandang Berpikir Deontologis, Teologis, Dan Kontektual - Riana Lum (Jurnal Ilmu Sosial Dan Politik, 2022)
Ethics is very important role in self-students and others, by understanding the role of ethical students can act on its production in asking students as for example in the study of demonstrating demanding ethical justice into a control tool that can withstand students from acting anarchist. As an students must understand freedom and responsibility, because many students who are monitimate of interpreting freedom with unparalleled freedom. Contrary to the ethics of deontology, theological ethics may judge whether an act is good based on the purpose it is intended to achieve it. It is another matter of ethical contextual portrayal of a collection of views in philosophy that emphasizes the context in which an action, speech or phrase occurs, and argues that, in some respects, action, speech, or phrase can only be understood relative to that context. Ethics is a picture / image of one person to be known.